SERVICE QUALITY ROOM BOY DURING PANDEMIC COVID-19 AT FOUR POINTS BY SHERATON BATAM - Yudi "; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tourism is one of the centers of attention that is very concerned by the government in solving the country's economic problems. However, since the arrival of Covid- 19, tourism has been the sector that has been hit the hardest due to the closure of access to leave the country and the difficulty of getting people out of an area. During the Covid-19 pandemic, tourism development in Indonesia began to declineso that the number of tourist visits, both domestic and non-domestic, decreased. Along with the decline in visitor levels in 2020-2021, the demand for accommodation is also decreasing. Currently, one of the four-star hotels that has survived the Fours Pount By Sheraton Batam pandemic is one of the four-star hotelsin Batam that has a room boy service procedure that good and wise this has an impact on the occupancy of Fours Point By Sheraton is still in Stable condition. Room Boy is part of housekeeping who is responsible for the tidiness, beauty, cleanliness and comfort of rooms, both occupied and vacant. Therefore, this study aims to determine the procedure for room boy service during the covid 19 pandemic.at Four Point By Sheraton Batam. This study uses descriptive quantitative methods to analyze problems based on data collection techniques in the form of observation,interviews, and documentation and questionnaires. The room boy service procedurewas carried out in order to improve the service of the four points hotel guest room facilities by sheraton batam during the covid-19 pandemic. Based on the results of the research that has been done, for the overall results of interviews, documentation and questionnaires, it can be concluded that the Service Procedure for Room Boy Fours Point By Sheraton Batam has been running according to the procedures thathave been carried out. Keywords: Hotel, Room Boy, Quality